2013
DOI: 10.1088/0953-4075/46/24/245202
|View full text |Cite|
|
Sign up to set email alerts
|

The creation, destruction, and transfer of multipole moments in electron- and proton-impact ionization of atoms and ions

Abstract: Expanding on previous works that involved elastic and inelastic scattering of electrons by atoms and ions, we use the wave-packet propagation scheme of Dollard to define multipole moment creation, destruction and transfer cross sections for electron- and proton-impact ionization of atoms and ions. The electron-impact cross sections can then be used by defining appropriate rate coefficients for use in Fujimoto’s population-alignment collisional-radiative model for cylindrically symmetric plasmas. Our result for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 62 publications
(138 reference statements)
1
13
0
Order By: Relevance
“…This is a follow-up to the first corrigendum which was reported in [2] to correct errors of a similar nature in another previously reported work [3]. The source of all those errors resides in the treatment of charged-particle scattering and the subtle manipulations made to obtain some of the equations in both [1,3]. All equation numbers cited here correspond to those of [1] unless specified otherwise.We found that equation ( 8), along with equations ( 10) and ( 15) which lead to the formula given by equation ( 17), are erroneous.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…This is a follow-up to the first corrigendum which was reported in [2] to correct errors of a similar nature in another previously reported work [3]. The source of all those errors resides in the treatment of charged-particle scattering and the subtle manipulations made to obtain some of the equations in both [1,3]. All equation numbers cited here correspond to those of [1] unless specified otherwise.We found that equation ( 8), along with equations ( 10) and ( 15) which lead to the formula given by equation ( 17), are erroneous.…”
mentioning
confidence: 66%
“…
The present corrigendum is dedicated to correcting unfortunate errors made in certain equations of our paper [1]. We should first stress the point that those errors have no serious consequences on the main results of the paper and most derived equations remain valid.
…”
mentioning
confidence: 94%
“…, 0 0, , 5 ¹ ¢ Following now the procedure of Joachain [11] and Csanak et al [17], we take the derivative of the left-hand side of equation (5) with respect to t and the t ¢  -¥ limit to obtain for the rate coefficient the formula…”
Section: The Derivation Of the Recombination Rate Formula Via The Ggw...mentioning
confidence: 99%
“…In our previous work [1], hereafter referred to as I, the wavepacket formalism of scattering has been used for the quantum mechanical definition of multipole moment creation, destruction and transfer rate coefficients for three-body electron-ion recombination. The same formalism has been used earlier for the treatment of the multipole moment cross section problem for electron-atom and electron-ion scattering [2][3][4] and for electron-and proton-impact ionization of atoms and ions [5]. Such cross sections play an important role in the population-alignment collisional-radiative model (PACR) of Fujimoto and collaborators [6][7][8] intended for the modeling of plasmas with cylindrically symmetric electron velocity distributions.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier works, Csanak et al discussed the creation, destruction and transfer of multipole moments in electron scattering by ions [28], by electron-impact ionization of ions [29], and in electron-ion three-body recombination [30]. Thus with the kinetic equations developed here for highly charged ions, the theoretical foundation of the complete PACR calculational scheme for such systems has been formally realized.…”
Section: Introductionmentioning
confidence: 97%